2001
DOI: 10.1289/ehp.01109937
|View full text |Cite
|
Sign up to set email alerts
|

Formation of strong airway irritants in mixtures of isoprene/ozone and isoprene/ozone/nitrogen dioxide.

Abstract: We evaluated the airway irritation of isoprene, isoprene/ozone, and isoprene/ozone/nitrogen dioxide mixtures using a mouse bioassay, from which we calculated sensory irritation, bronchial constriction, and pulmonary irritation. We observed significant sensory irritation (approximately 50% reduction of mean respiratory rate) by dynamically exposing the mice, over 30 min, to mixtures of isoprene and O3 or isoprene, O3, and NO2. The starting concentrations were approximately 4 ppm O3 and 500 ppm isoprene (+ appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
1
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(34 citation statements)
references
References 42 publications
0
31
1
2
Order By: Relevance
“…Subsequently, Alarie et al (27) demonstrated that some "reactive" species trigger symptoms that do not follow this predictable pattern and therefore that irritation from reactive species must be caused by a different mechanism. Weschler and Shields (28) and Wilkins et al (29) have examined the relationships of reactive species with such relatively nonreactive agents and shown that "indoor chemistry" produces far more irritating substances at a ratio of 2:1 compared with the initial nonirritating agent. Indoor chemistry in this context refers to the reactions of compounds such as ozone and nitrogen oxides with relatively inert VOCs in a fashion that oxidizes them and produces two more irritating for each single previously inert molecule.…”
Section: Mucosal Irritationmentioning
confidence: 99%
“…Subsequently, Alarie et al (27) demonstrated that some "reactive" species trigger symptoms that do not follow this predictable pattern and therefore that irritation from reactive species must be caused by a different mechanism. Weschler and Shields (28) and Wilkins et al (29) have examined the relationships of reactive species with such relatively nonreactive agents and shown that "indoor chemistry" produces far more irritating substances at a ratio of 2:1 compared with the initial nonirritating agent. Indoor chemistry in this context refers to the reactions of compounds such as ozone and nitrogen oxides with relatively inert VOCs in a fashion that oxidizes them and produces two more irritating for each single previously inert molecule.…”
Section: Mucosal Irritationmentioning
confidence: 99%
“…Among the various harmful gases, nitrogen oxides (NO x ) have a negative impact through the smog and acid rain formations as well as the decrease of the superior ozone layer [1,2]. Several methods have been applied for nitrogen oxides elimination including the reduction of NO x by selective non-catalytic reduction (SNCR) and selective catalytic reduction (SCR) [3].…”
Section: Introductionmentioning
confidence: 99%
“…First, airway irritation has been reported in mice exposed to terpene oxidation products (Wolkoff et al 2000;Clausen et al 2001;Wilkins et al 2001;Rohr et al 2002). These observed effects may be related to the chemical composition of the OPs since many of them contain C O, COOH, and OH functional groups and may interact with cellular material.…”
Section: Introductionmentioning
confidence: 99%
“…We used 2 different monoterpenes, α-pinene and d-limonene, as well as a hemiterpene, isoprene, as each of these reaction systems yields different products and the reaction rates with ozone vary. Furthermore, toxicological work by Wolkoff et al (2000), Clausen et al (2001), Wilkins et al (2001), and Rohr et al (2002) used the same 3 terpenes and found different degrees of irritation from each mixture, with isoprene having the largest effect. As such, we report the characterization of a reaction system designed to allow the generation and quantification of ultrafine particles as well as to conduct exposure experiments using mice.…”
Section: Introductionmentioning
confidence: 99%